Can Health Insurance Improve the Happiness of the Romanian People? - Gabriela Mihaela Muresan; Codruta Mare; Dan Tudor Lazar; Sorin Paul Lazar (Amfiteatru Economic, 2023)
Developing a strategy to increase happiness is a major focus of a positive economy. The purpose of the present study is to find an answer to the following question: can insurers contribute to happiness? Starting from the ANOVA approach and regression analysis on the Romanian sample, we show that financial factors, self-rated stress level, age, and private health insurance affect the level of reported happiness. This is one of the first Romanian studies to approach happiness from the perspective of a financial health insurance product. From another perspective, for people without health insurance, income is a key factor of influence. Thus, our paper is primarily addressed to insurers who want to improve their sales techniques and to all insureds who want to know other benefits that appear after signing a health insurance policy.
Keywords: G22; 330; Happiness; income; health insurance; Romania.